2013
DOI: 10.4236/psych.2013.43022
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence, Alcohol Consumption and Depression in Criminal Population

Abstract: The objective of this research was to determine the differences in levels of domestic violence, alcohol and depression by type of crime committed on 259 men and 200 women inmates of the Centre for Social Rehabilitation in Mexico. To assess alcohol consumption indicators were adapted from the National Addiction Survey, the CES-D was used to measure depressive symptoms and in terms of domestic violence, we designed a 16-reactive scale evaluating: verbal aggression, physical aggression, humiliation and respect. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…Respecto a las diferencias en las prevalencias, resalta que mientras en reclusos hombres son más frecuentes los trastornos de ansiedad, psicóticos y antisocial de la personalidad, concurrentes con los trastornos por consumo de alcohol y por uso de cannabis, en las mujeres se presentan más los trastornos afectivos, de alimentación, por déficit de atención, de estrés postraumático y límite de la personalidad, concurrentes con el consumo de alcohol y estimulantes (Butler et al, 2011;Konstenius et al, 2015;Martínez-Lanz & Fernández Díaz, 2013;Zlotnick et al, 2008). Sobre diferencias de género en factores de riesgo, se ha visto que en hombres el abuso físico en la infancia predice más la PD, mientras que en las mujeres, el abuso sexual tiene un mayor valor predictivo (Villagrá et al, 2013).…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified
See 2 more Smart Citations
“…Respecto a las diferencias en las prevalencias, resalta que mientras en reclusos hombres son más frecuentes los trastornos de ansiedad, psicóticos y antisocial de la personalidad, concurrentes con los trastornos por consumo de alcohol y por uso de cannabis, en las mujeres se presentan más los trastornos afectivos, de alimentación, por déficit de atención, de estrés postraumático y límite de la personalidad, concurrentes con el consumo de alcohol y estimulantes (Butler et al, 2011;Konstenius et al, 2015;Martínez-Lanz & Fernández Díaz, 2013;Zlotnick et al, 2008). Sobre diferencias de género en factores de riesgo, se ha visto que en hombres el abuso físico en la infancia predice más la PD, mientras que en las mujeres, el abuso sexual tiene un mayor valor predictivo (Villagrá et al, 2013).…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified
“…Sobre diferencias de género en factores de riesgo, se ha visto que en hombres el abuso físico en la infancia predice más la PD, mientras que en las mujeres, el abuso sexual tiene un mayor valor predictivo (Villagrá et al, 2013). También se ha documentado que entre las mujeres reclusas existe una mayor probabilidad de presentar conductas suicidas (Lukasiewicz et al, 2009) y se reporta una mayor violencia doméstica que en los hombres (Martínez Lanz et al, 2013).…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified
See 1 more Smart Citation
“…Furthermore, men who attempted and completed suicide were more likely to express violence as a child than women, but no gender differences were found in expressed violence in adulthood (Jokinen et al, 2010). One study demonstrated that severely depressed men in an incarcerated population were most commonly detained for causing bodily harm (Lanz & Díaz, 2013). Finally, a Swedish population study found that 14% of men with depression committed a violent crime, which included but was not limited to homicide, assault, or any sexual offense, compared with 2% of women with depression (Fazel et al, 2015), suggesting that the ultimate escape behavior may also include homicide and not just suicide.…”
Section: Introductionmentioning
confidence: 99%